Attitudes toward pharmacy‐based HCV/HIV testing among people who use drugs in rural Kentucky. Issue 1 (5th March 2021) - Duong, Michelle; Delcher, Chris; Freeman, Patricia R.; Young, April M.; Cooper, Hannah L.F.
Abstract: Purpose: Rural areas of the United States have experienced outbreaks of human immunodeficiency virus (HIV) and hepatitis C virus (HCV) infections among people who use drugs (PWUD). Pharmacy‐based interventions may play a crucial role in prevention and entry into care, especially when traditional health care access is limited. The willingness of rural PWUD to use pharmacies for HIV/HCV‐related services remains unknown. The purpose of this study was to describe the factors associated with the perceived likelihood of participating in free pharmacy‐based HIV and HCV testing among PWUD living in rural Kentucky. Methods: Baseline data from the CARE2HOPE study in five Appalachian counties in eastern Kentucky were used. Participants were recruited using respondent‐driven sampling and completed interviewer‐administered surveys. Guided by the Andersen and Newman Framework of Health Services Utilization, we examined distributions and correlates of items regarding willingness to participate in free pharmacy‐based HIV/HCV testing using logistic regression. Analyses included individuals who reported being HIV ( N = 304) or HCV ( N = 185) negative. Findings: Seventy‐five percent of PWUD reported being "very likely" to participate in free pharmacy‐based HIV testing and 80% for HCV testing. Two factors were associated with being less willing to participate in free HIV testing: PWUD who previously tested for HIV (OR: 0.47, CI: 0.25–0.88) and PWUD who obtained a high school diploma or equivalent compared to those who completed less (OR: 0.50, CI: 0.26–0.99). Conclusion: Free pharmacy‐based HIV and HCV testing was invariably acceptable among most of the rural PWUD in our sample, suggesting that pharmacies might be acceptable testing venues for this population.